A possible relationship of human leucocyte antigens with psoriasis vulgaris and geographic tongue. (29th August 2014) - Picciani, B.L.S.; Carneiro, S.; Sampaio, A.L.B.; Santos, B.M.; Santos, V.C.B.; Gonzaga, H.F.S.; Oliveira, J.C.; Porto, L.C.; Dias, E.P.
Abstract: Background: Geographic tongue (GT) is the most frequent oral lesion in psoriatic patients (PP), and genetic involvement in these conditions has been described. The association of psoriasis with GT is still not clear, and the study of human leucocyte antigen (HLA) may help clarify this relation. Objective: The aim of this study was to investigate the association of HLA alleles with psoriasis vulgaris and GT. Methods: Fifty‐eight Brazilian PP, 29 GT patients and 125 healthy controls individuals were selected. Information on demographic and clinical characteristics was collected. All patients underwent an oral examination and blood collection for HLA typing. Results: HLA‐A did not show significant differences in frequencies among the groups. HLA‐B*57 allele was more frequently found in PP and was not found in GT. HLA‐B*58 allele was more frequently found in GT. HLA‐C*06 and ‐C*18 alleles were associated with psoriasis. No significant differences in HLA‐DRB1 and HLA‐DQB1 were observed. Conclusion: HLA‐B*58 was associated with GT and HLA‐B*57 was possibly associated with psoriasis. This suggested that some GT cases may represent true oral psoriasis and some may represent only GT. Therefore, it is necessary to make this distinction and increase our sample size to improve the correct diagnosis and treatment of these conditions.